2003
DOI: 10.1063/1.1596720
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric transition in an epitaxial barium titanate thin film: Raman spectroscopy and x-ray diffraction study

Abstract: We have performed x-ray diffraction and Raman spectroscopy measurements in the temperature range of 300–873 K on a single phase epitaxially oriented BaTiO3 thin film grown by pulsed laser deposition on a single crystal MgO substrate. The θ–2θ room temperature diffraction measurements and asymmetric rocking curves indicate that the film is very weakly tetragonal with the c-axis parallel to the plane of the film. X-ray diffraction measurements up to high temperature reveal only a change in slope in the perpendic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 36 publications
8
86
0
Order By: Relevance
“…In the case of BaTiO 3 , the formation mechanism from solution-derived precursor is complicated and has been argued for a long time [24]. Considering the general formation mechanism, it has been reported that BaTiO 3 forms either by a nucleation process at the BaCO 3 /TiO 2 interface or through a decomposition of crystalline Ba 2 Ti 2 O 5 CO 3 intermediate phase [19][20][21][22][23].…”
mentioning
confidence: 99%
“…In the case of BaTiO 3 , the formation mechanism from solution-derived precursor is complicated and has been argued for a long time [24]. Considering the general formation mechanism, it has been reported that BaTiO 3 forms either by a nucleation process at the BaCO 3 /TiO 2 interface or through a decomposition of crystalline Ba 2 Ti 2 O 5 CO 3 intermediate phase [19][20][21][22][23].…”
mentioning
confidence: 99%
“…Although the crystal structure of fully grown nanocrystals appears cubic from x-ray diffraction data, Raman spectroscopy and pair distribution function analysis demonstrate the presence of non-centrosymmetric regions arising from the off-centering of the titanium atoms [53][54][55]. Room temperature polarization switching was also demonstrated down to ∼5 nm in size for individual nanocrystals [56].…”
Section: Dielectric Properties Of Bst/pfa Nanocomposite Thin Filmsmentioning
confidence: 96%
“…Room temperature polarization switching was also demonstrated down to ∼5 nm in size for individual nanocrystals [56]. In terms of eigen-lattice vibrations and Raman active order-disorder of the cubic BT(BST) nanocrystals [15,54,57,58], the dielectric constant of the room temperature cubic phase should be mainly due to the order-disorder feature and its coupling with A1 modes, i.e. c axis dielectric behavior resides in the cubic phase.…”
Section: Dielectric Properties Of Bst/pfa Nanocomposite Thin Filmsmentioning
confidence: 99%
“…BTO thin films are of significant interest for a variety of technological applications, such as multilayer ceramic capacitors, sensors, actuators, thermistors, dynamic random access memory, and electroluminescent elements [1][2][3]. A variety of methods, such as sputtering, metal organic chemical vapor deposition, pulsed laser deposition, and chemical solution deposition, have been investigated to prepare BTO thin films [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%